Planning of Steady Industrial Enterprise Development under Condition of Environment Instability - Naberezhnyh, T.S.; Shevchenko, N.Y. (Економічний вісник Донбасу, 2015)
The problem of search fundamentally of another methods of planning of activity and development of enterprise comes into question in the conditions of environment instability. It is marked that the mechanism of planning of steady development of industrial enterprise offered in scientific literature requires a further study and perfection in the context of becoming of Ukraine as a competitive participant of world trade. The improved conceptual model of planning of steady development of industrial enterprise is described in the article, that, unlike other approaches, is based on the stage-by-stage design of process of planning of activity of enterprise, providing quality transformation of enterprise as a difficult system and allowing to define the effective trajectory of his steady development. It is suggested to use the method of multisigmoid approximation for prognostication of basic economic indicators on the nearest periods. On the basis of prognosis values it is suggested to form the trajectory of development of enterprise and conduct the estimation of stability of the chosen trajectory. Обговорюється проблема пошуку принципово інших методів планування діяльності й розвитку підприємства в умовах нестабільності зовнішнього середовища. Відмічено, що пропонований в науковій літературі механізм планування стійкого розвитку промислового підприємства вимагає подальшого вивчення і вдосконалення в контексті становлення України як конкурентоздатного учасника світової торгівлі. У статті описана концептуальна модель планування стійкого розвитку промислового підприємства, яка, на відміну від інших підходів, базується на поетапному моделюванні процесу планування діяльності підприємства, що забезпечує якісну трансформацію підприємства як складної системи і дозволяє визначити ефективну траєкторію його стійкого розвитку. Пропонується використовувати метод мультисигмоїдальної апроксимації для прогнозування основних економічних показників на найближчі періоди. На основі прогнозних значень пропонується формувати траєкторію розвитку підприємства та здійснювати оцінку стійкості обраної траєкторії. Обсуждается проблема поиска принципиально иных методов планирования деятельности и развития предприятия в условиях нестабильности внешней среды. Отмечено, что предлагаемый в научной литературе механизм планирования устойчивого развития промышленного предприятия требует дальнейшего изучения и совершенствования в контексте становления Украины как конкурентоспособного участника мировой торговли. В статье описана усовершенствованная концептуальная модель планирования устойчивого развития промышленного предприятия, которая, в отличие от других подходов, базируется на поэтапном моделировании процесса планирования деятельности предприятия, обеспечивающего качественную трансформацию предприятия как сложной системы и позволяющего определить эффективную траекторию его устойчивого развития. Предлагается использовать метод мультисигмоидальной аппроксимации для прогнозирования основных экономических показателей на ближайшие периоды. На основе прогнозных значений предлагается формировать траекторию развития предприятия и проводить оценку устойчивости выбранной траектории.